Sport MOMsumers: A Modern Reexamination of the Role That Mothers Play in their Families’ Professional Sport Consumption - Jessica R. Braunstein-Minkove; Jennifer L. Metz (Journal of Applied Sports Management, 2019)
As the role of women and, therefore, mothers has changed, so too, has their place in their families’ professional sport consumption experience. This qualitative assessment, including a demographic and consumption snapshot, provides insight into the perspective of mothers in their families’ professional sport consumption habits and intentions. Primary findings fall under the themes of Personal Priorities and Constraints. While Constraints drove the conversation, this group of women was interested in maintaining and sharing the role of sport in their lives. As such, minimal- investment recommendations are made to address the concerns that mothers have with many of these items. Subscribe to JASM
Keywords: Consumer behavior; female market; segmentation; sport marketing